PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENGGELAPAN BARANG SITAAN - Novita Novita (Belom Bahadat, 2020)
This paper analyzes the law enforcement of the perpetrators of the embezzlement of the confiscated goods and the purpose of the writer to raise this title is to find out about law enforcement and supervision in the embezzlement of the confiscated goods. To analyze the title that the author adopted, empirical juridical research methods, namely research on the problem by looking at and observing the applicable legal norms associated with the facts that exist from the problems encountered in the study. The result showed that for law enforcement when viewed substantially there are rules governing only that there are deficiencies in terms of structure where there is a shortage of personnel to guard and care for the existing confiscated state goods and the narrow field to accommodate the confiscated goods and also for their own supervision has been carried out even though the procedure was just that there was still negligence in terms of recording the registration of confiscated goods.